Analysis of The Architecture and Decoration of Isfahan Masjid-E Jameh in Syntactic Dimension - Çakıroğlu, Birgül; Akat, Reyhan (Technium Social Sciences Journal, 2024)
In this research, the general architectural features and decorations of the Friday Mosque of İsfahan, Iran, which belongs to the 11th century Great Seljuk State period, one of the most important works of Islamic architecture, are examined. This mosque, which is also called Atiq Mosque, Masjid-e Jameh and Great Mosque today, is among the most important structures that have witnessed hundreds of years of history. This study on the expressibility of the semantic dimension of the structure in the syntactic dimension is important in terms of its contribution to the literature. For this purpose, information about the Great Seljuk mosque architecture and the historical development process of Friday Mosque in terms of architecture is given and the subject and purpose of the researches on this mosque are stated. Then, the method to be used in expressing the architectural structure and decorations in the syntactic dimension is explained. In order to obtain the data about the mosque, on-site visual-observation and examination technique and photography technique were used. Basic design principles were used in the analysis of the data. As a result, the architectural features and ornamental motifs used in this mosque, which is an important mosque of the Great Seljuk period, have been revealed with this method. The findings obtained about the structure and ornaments can be used in religious buildings as well as other architectural structures, ornaments, clothing, furniture and decoration